Should Cross-border Services between Austria and Slovenia Still be Restricted? An Economic Assessment of the Existing Market Regulations - Thomas Döring; Birgit Aigner (Austrian Institute of Economic Research (WIFO), 2009)
In 2004 the Republic of Slovenia entered the European Union and, as a matter of principle, was guaranteed the four freedoms (free trans-national mobility of goods, services, capital and labour). From an economic viewpoint, this guarantee should provide the required institutional framework to maximise social benefits within the internal market. However, with respect to cross-border services a set of temporary regulations exists, all of which initially for two years and subsequently for further three years, were implemented to restrict the free movement of services partially in order to protect Austrian regions against labour market disadvantages. The restrictions were extended in 2009 for two additional years (until 2011). These temporary restrictions indicate the familiar trade-off between expected efficiency and welfare gains of a completely integrated common market in the medium and long run, and - as a result of intensified transnational business activities - potential socioeconomic losses for certain regions or economic sectors in the short run. Against this background, the paper asks for the economic usefulness of the afore-mentioned restrictions of cross-border service activities between Austria and Slovenia. Thereby, the question whether these (temporary) regulations should have been continued until 2011 or be abolished immediately is of particular importance. To be able to provide an answer to this question, the topic is analysed in four steps: First, the expected welfare effects of cross-border service restrictions will be outlined by discussing the impact of such regulations on the efficient allocation of resources as well as the pace of economic change. Therefore, theoretical and empirical insights concerning the economic effects of international trade with services will be considered. Secondly, the paper analyses the empirical situation of cross-border trade in goods and services between Austria and Slovenia in order to argue that Austria has a "double dividend" with respect to the existing regulatory system. In part three, the question is asked to what extend a complete liberalisation of cross-border services would affect Austrian regions economically, if one takes into account the geographically limited market radius of the currently regulated service industries. Finally, the status-quo analysis of the existing restrictions of cross-border services between Austria and Slovenia provides a background to derive policy recommendations.
Keywords: 330; international trade; trade policy; Austria; Slovenia; services; economic integration; restrictions; Grenzüberschreitender Verkehr; Dienstleistungshandel; Österreich; Slowenien; EU-Binnenmarkt; Handelshemmnisse; Wirkungsanalyse